Dihydromyricetin attenuates age-related macular degeneration: pharmacological effects and exploration of putative targets - Zhou, Hongyu; Pang, Jianhui; Wu, Baiyang; Zhuang, Yanan; Li, Shenjun; Jiang, Jing (Frontiers in Pharmacology, 2025)
IntroductionAge-related macular degeneration (AMD) is a leading cause of vision loss in older adults, with limited effective treatments available. This study aimed to investigate the pharmacological effects of dihydromyricetin (DHM) on AMD and to identify its putative pharmacological targets through network analysis and molecular docking approaches.MethodsIn vitro experiments established an AMD model using sodium iodate (SI)-induced ARPE-19 cells, with CCK-8 assays determining 15 mM SI as the optimal modeling concentration and 100 μM DHM as the optimal treatment concentration. For in vivo validation, an AMD model was generated in C57 mice via tail vein injection of SI (30 mg/kg). Subsequent oral gavage with DHM (50 or 100 mg/kg) was administered. Integrated network analysis, molecular docking, and RT- qPCR validation were employed.ResultsRT-qPCR analysis revealed that DHM reversed SI-induced aberrant expression of AMD-associated biomarkers (ICAM-1, APOE, HTRA1, ABCA4). Light microscopy and flow cytometry demonstrated DHM's significant mitigation of SI-triggered cellular morphological alterations and apoptosis (35% reduction). Western blot analysis further confirmed DHM-mediated suppression of apoptosis through regulation of p53, Bax, cleaved caspase-3, and Bcl-2 expression. High-dose DHM significantly attenuated retinal thinning (10.7% reduction), decreased pigment loss, and ameliorated structural disorganization in the outer nuclear layer (ONL). These analyses predicted seven putative targets implicated in functional categories including neurodegeneration, apoptosis, and DNA modification. Subsequent PPI network construction and GO/KEGG enrichment analyses revealed these targets' involvement in biological processes such as angiogenesis and extracellular matrix organization.ConclusionIn conclusion, the present study demonstrates that DHM can mitigate AMD-related damage in both in vitro and in vivo models, while predicting putative targets and signaling pathways through which DHM may exert its effects against AMD. These findings offer promising directions for the development of AMD therapies and lay the groundwork for further investigation into DHM as a candidate drug for treating and preventing AMD.